Primary vulval sebaceous carcinoma: rare case report and literature review - Pei, Kaige; Zhang, Jiawen; Xi, Mingrong (Frontiers in Oncology, 2025)
This study presents a rare case of primary vulval sebaceous carcinoma (SC) and a literature review. Sebaceous carcinoma is an aggressive skin malignancy, predominantly periocular, with extraocular cases being particularly uncommon. We detail a 50-year-old female patient diagnosed with primary vulval SC, exhibiting a 0.5 cm white lesion on her left vulva. Despite initial drug therapy, the lesion progressed to ulceration and induration. Histopathological examination confirmed SC. The patient underwent extensive local vulvectomy and sentinel lymph node biopsy, showing no evidence of metastasis. At 22 months post-surgery, the patient remained recurrence-free. A literature review identified 13 additional cases, highlighting diverse presentations and management strategies. Our findings underscore the importance of sentinel lymph node biopsy and tailored surgical approaches for early-stage disease. The study contributes to the understanding of this rare condition and may inform future management protocols.